Genome-Wide Profiling of Cardinium-Responsive MicroRNAs in the Exotic Whitefly, Bemisia tabaci (Gennadius) Biotype Q - Li, Hongran; Wei, Xiaoying; Ding, Tianbo; Chu, Dong (Frontiers in Physiology, 2018)
Although the bacterial symbiont, Cardinium, has profound effects on the ecological adaptation of its host whitefly, Bemisia tabaci (Gennadius) Q, the molecular mechanism underlying their interactions remains poorly understood. MicroRNAs (miRNAs) are numerous non-coding small RNAs (sRNAs) that are involved in ecological adaptation by manipulating metabolism, development, and epigenetic inheritance. Yet, the roles of miRNA remain unclear in the interactions between Cardinium and its host whitefly, B. tabaci Q. In this study, the sRNA libraries of Cardinium-infected and -uninfected B. tabaci Q with identical genetic background were constructed, amplified, and sequenced. Subsequently, the target genes of the differentially expressed miRNAs were predicted by integrating the B. tabaci Q genome data. A total of 125 known miRNAs and 100 novel miRNAs were identified, among which 23 significant differentially expressed miRNAs were identified in both libraries. The predicted potential targets of differentially expressed miRNAs are involved in extensive regulatory and metabolic pathways such as apoptosis, reproduction and development, immune response, thermotolerance and drug resistance. GO and KEGG pathways analysis revealed that some miRNA-target genes are closely associated with energy metabolism. In conclusion, comparison of the miRNA and genome data can provide a unique source of miRNAs and target genes to further explore insect-symbiont interactions, particularly elucidating the function of Cardinium in B. tabaci Q.